Effect of Green Tea Polyphenol Epigallocatechin-3-gallate on the Aggregation of αA(66-80) Peptide, a Major Fragment of αA-crystallin Involved in Cataract Development. (3rd October 2017) - Kumar, Vijay; Gour, Shalini; Peter, Ocan Simon; Gandhi, Shraddha; Goyal, Pankaj; Pandey, Janmejay; Harsolia, Ram Swaroop; Yadav, Jay Kant
ABSTRACT: Purpose : Crystallin is a major protein present in eye lens. Peptide fragment αA(66-80) derived from αA-crystallin possesses high aggregation propensity and forms amyloid-like structures. αA(66-80) aggregates are known to interact with soluble crystallins and destabilize native structures that subsequently undergo aggregation. Crystallin aggregation in eye lens leads to reduction in lens opacity, the condition generally referred to as a cataract. Thus, αA(66-80) aggregation appears to be an important event during cataract development, and therefore, inhibition of αA(66-80) aggregation may be an attractive strategy to intervene in cataract development. Materials and Methods : αA(66-80) peptide derived from αA-crystallin possesses high aggregation potential and has a crucial role in cataract development. In order to inhibit the aggregation of αA(66-80) peptide, epigallocatechin-3-gallate (EGCG), a major active constituent of green tea, was employed. The inhibitory effect was assessed by Congo Red (CR) spectral shift assay, Thioflavin-T binding assay, transmission electron microscopy and fluorescence microscopy. Results : The inhibitory potential of EGCG toward αA-crystallin was clearly observed as in the presence of EGCG, the αA(66-80) aggregation was considerably inhibited and the pre-formed fibrillary aggregates of αA(66-80) were found to be disassembled. Conclusion : In the present study, we are able to successfully demonstrate that EGCG efficiently blocks the aggregation of αA(66-80) peptide in a concentration-dependent manner. Furthermore, it is also evident that EGCG is able to disaggregate pre-formed αA(66-80) aggregates. The study suggests that EGCG can be a potential molecule that can prevent the initiation of cataract as well as be helpful in the disease reversal.